Interpreting and Contextualising the Histories (on E. Bowie, ed., Herodotus: Narrator. Scientist. Historian and T. Harrison and E. Irwin, edd., Interpreting Herodotus) - de Bakker, Mathieu (Histos, 2024)
n/a